2012
DOI: 10.2478/v10181-012-0075-6
|View full text |Cite
|
Sign up to set email alerts
|

The presence of anti-Hypoderma antibodies in udder milk samples, and correlation with selected parameters of dairy performance

Abstract: Hypodermosis is responsible for significant economic losses and remains a current problem in animal husbandry. This study determined the extent of Hypoderma spp. invasion in north-eastern Poland in dairy herds. The extent of the invasion, determined on the basis of positive results of an ELISA assay (Bovine Hypodermosis Milk Screening of Institut Pourquier), varied in herds. Statistical analysis performed on the results of milk productivity and content of basic components revealed a decrease in the milk yield … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 11 publications
(18 reference statements)
0
1
0
Order By: Relevance
“…However, as shown by later studies conducted by employees of the State Veterinary Institute in Pulawy, the extensiveness of infestation in Poland after the end of the program again reached the level of 20% to 100% of the population of cattle herds [11]. The studies carried out in the Warmia and Mazury voivodeship showed extensiveness of infestation at the level of 28% [21].…”
Section: Discussionmentioning
confidence: 99%
“…However, as shown by later studies conducted by employees of the State Veterinary Institute in Pulawy, the extensiveness of infestation in Poland after the end of the program again reached the level of 20% to 100% of the population of cattle herds [11]. The studies carried out in the Warmia and Mazury voivodeship showed extensiveness of infestation at the level of 28% [21].…”
Section: Discussionmentioning
confidence: 99%